Activation of Coagulation and Fibrinolysis Following OKT3 Administration to Renal Transplant Recipients: Association with Distinct Mediators - Raasveld, Maarten H M; Hack, C Erik; ten Berge, Ineke J M (Thrombosis and Haemostasis, 1992)
Treatment with OKT3 induces cytokine release and activates the complement system. Since both phenomena may affect coagulation and fibrinolysis we studied these systems in 8 renal transplant recipients during OKT3 treatment. In 8 of 9 patients a similar pattern was observed: plasma thrombin-antithrombin-III-complex, tissue-type plasminogen-activator and plasmin-α2-antiplasmin-complex levels were increased as compared to pretreatment levels (p <0.05) at 15 min after the first OKT3 dose and reached peak values at 1 h. No significant changes were observed upon subsequent OKT3 administrations or in a control group of 8 patients. In one patient upon the first OKT3 administration only complement activation, and no cytokine release was observed, whereas plasma thrombin-antithrombin-III-complex, tissue-type plasminogen-activator and plasmin-α2-antiplasmin-complex levels increased only at 15 min.In conclusion, we demonstrate a biphasic activation of coagulation and fibrinolysis upon the first OKT3 dose; the initial phase seems to be associated with complement activation, the later phase with cytokine release.